Increased risk of cardiovascular disease among kidney cancer survivors: a nationwide population-based cohort study - Jung, Minji; Choo, Eunjung; Li, Shufeng; Deng, Zhengyi; Li, Jinhui; Li, Mingyi; Basran, Satvir; Lee, Sukhyang; Langston, Marvin E.; Chung, Benjamin I. (Frontiers in Oncology, 2024)
Background: Cardiovascular disease (CVD) is a major concern of morbidity and mortality among cancer survivors. However, few evidence exists on the short-and long-term risk of CVD in kidney cancer (KCa) survivors.In this nationwide, large population-based retrospective cohort study, we used the Korean national health insurance and medical checkup survey linkage database (2007-2021), drawn from the entire Korean population. We included adults diagnosed with KCa as the first primary cancer and matched them to an individual without KCa at a 1:5 ratio. The primary outcome was CVD incidence, including myocardial infarction, stroke, atrial fibrillation, heart failure, peripheral arterial occlusion, and venous thromboembolism (VTE). We evaluated CVD risk at 6 months, 1 year, and 5 years following cancer diagnosis, using Fine-Gray competing risk models that accounted for death as a competing factor.Results: A total of 149,232 participants were included (KCa survivors: N=20,093 and matched non-KCa individuals: N=129,139). After 6-month follow-up, KCa survivors showed an increased risk of CVD compared to the general population (subdistribution hazard ratio (HR) 2.70, 95% confidence interval (CI) 2.31-3.15). After 1 year, KCa survivors had a higher risk of CVD (HR=1.77, 95% CI: 1.56-2.00). After 5 years, this elevated CVD risk remained (HR=1.10, 95% CI: 1.03-1.18), with VTE identified as the primary contributing disease (HR=3.05, 95% CI:2.59-3.59).KCa survivors had an increased risk of CVD up to 5 years after cancer diagnosis compared to the general population. Our findings emphasize the importance of comprehensive healthcare management for both CVD and KCa throughout cancer survivorship.